Bioremediation of vegetable and agrowastes by Pleurotus ostreatus: a novel strategy to produce edible mushroom with enhanced yield and nutrition - Singh, V. K.; Singh, M. P. (Cellular and Molecular Biology, 2014)
Pleurotus ostreatus was grown on paddy straw as well as other vegetable and agricultural wastes i.e. pea pod shell, cauliflower leaves, radish leaves and brassica straw in various combinations with paddy straw. The mushroom did not grow on the vegetable wastes separately. The cumulative yield and biological efficiency of the edible oyster mushroom P. ostreatus grown on substrate containing paddy straw in various combinations with different vegetable wastes i.e. 20% and 30 % vegetable wastes mixed with 80% and 70% (w/w) of paddy straw was found to be better, when compared with yield and biological efficiency obtained on paddy straw (100%) alone. The protein content and six essential amino acid contents (Leu, Ile, Val, Thr, Met, Phe) showed a significant increase and total sugar and reducing sugar contents showed decrease in the mushroom fruit bodies grown at different combinations of vegetable wastes with paddy straw as compared to paddy straw alone. However, there was not any significant change in moisture content of mushroom cultivated on different groups of wastes. Hence, results of this investigation suggest that the vegetable wastes which are generally left to rot in situ in many cities and villages causing outbreak of diseases can be bioremediated by edible mushroom P. ostreatus. The added advantage is that we get edible mushroom fruit body with improved nutrition.